Successful Closed Reduction of a Lateral Elbow Dislocation - Kenya Watanabe; Takuma Fukuzawa; Katsuhiro Mitsui (Case Reports in Orthopedics)
In this report, we present a case of lateral elbow dislocation treated with closed reduction. Lateral elbow dislocation is rare, and a closed reduction is reported with even less frequency. The reduction can be hindered by swelling and soft tissue interposition, and we describe the use of a nonoperative reduction technique performed under mild sedation with early physiotherapy to avoid joint stiffness. No additional complication was observed, and the normal range of elbow movement and function was obtained by early physiotherapy.